2002
DOI: 10.1186/1471-2091-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Drosophila acetylcholinesterase stability by elimination of a free cysteine

Abstract: Background Acetylcholinesterase is irreversibly inhibited by organophosphate and carbamate insecticides allowing its use for residue detection with biosensors. Drosophila acetylcholinesterase is the most sensitive enzyme known and has been improved by in vitro mutagenesis. However, it is not sufficiently stable for extensive utilization. It is a homodimer in which both subunits contain 8 cysteine residues. Six are involved in conserved intramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The reason for this activity loss is seen in the humidity of the enzyme layer when stored at room temperature overnight. The negative effect of moisture on the stability of AChE was already reported elsewhere. , We also tested the reactivation of the biosensor, a further criterion for its functionality. The AChE activity of the new and 17-month-old biosensors could be completely reactivated after each measurement using 2-PAM.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The reason for this activity loss is seen in the humidity of the enzyme layer when stored at room temperature overnight. The negative effect of moisture on the stability of AChE was already reported elsewhere. , We also tested the reactivation of the biosensor, a further criterion for its functionality. The AChE activity of the new and 17-month-old biosensors could be completely reactivated after each measurement using 2-PAM.…”
Section: Resultsmentioning
confidence: 68%
“…In the case of Torpedo marmorata 23 and D. melanogaster AChE, problems in enzyme stability were reported. Several approaches were performed to increase the stability of AChE, for example, by adding protective compounds or, in the case of the D melanogaster AChE, by protein engineering . The exchange of a cysteine residue, which is not involved in an intra- or intermolecular disulfide bridge, by valine increased the temperature stability of the D. melanogaster AChE.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the negative consequences on protein structure caused by thiol adduct formation of buried free cysteines, mutational substitution of such residues is often accompanied by a notable increase in functional half-life. [9][10][11][12][13] An analysis of a set of 131 nonhomologous singledomain protein X-ray structures (1.95 Å resolution or better) by Petersen et al reported that the prevalence of free-cysteine residues in proteins is 0.5% (or, typically, one free cysteine in an average size protein); furthermore, 50% of these free cysteines are buried within the protein interior. 14 Thus, although potentially highly problematic for protein therapeutic application, the presence of buried free cysteines in proteins is a surprisingly common occurrence; some familiar examples include fibroblast growth factors (FGFs), interleukin-2, β-interferon, granulocyte colony-stimulating factor, and insulin-like growth factor-binding protein-1 (with the majority of these being approved human therapeutics).…”
Section: Introductionmentioning
confidence: 99%
“…However, the –SH groups of free cysteine residues can easily be oxidized by metal ions such as Cu 2+ , which negatively affects protein folding [ 22 ]. The introduction of a suitable couple of cysteine residues to form a stable covalent bond and the substitution of a cysteine residue with different amino acids was proven effective in eliminating the negative effect of free –SH groups [ 23 , 24 ]. There are many successful cases of cysteine residues substituted by alanine, serine, and valine for increasing the thermostability of enzymes [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%